Painted Skin : Negotiating Mainland China's Fear of the Supernatural. Issue 1 (1st March 2011) - Willis, Andy
Following Hong Kong's reunification with China in 1997, it became a "Special Administrative Region" (SAR). This meant that Hong Kong filmmakers now had wider access to distribution and co-production deals with the mainland. In this article, through a case study of the 2008 film, Painted Skin, I consider how the makers of a supernaturally based work have negotiated these industrial changes within their film, in particular, the stricter censorship laws in operation on the mainland. The article argues that while Painted Skin is adapted from a familiar source and in a long tradition of Hong Kong horror films, the historically specific set of circumstances operating around its production and release reveal how central this historical specificity is to any understanding of it as a contemporary Hong Kong horror film.